2020
DOI: 10.21203/rs.3.rs-104039/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment the Risk Perception of Health Care Workers of Covid-19 Disease

Abstract: Background and Objectives: The emergent Covid-19 disease with conspicuous prevalence is putting the healthcare workers' job security at risk. The preventive behaviors in every individual have a close relationship with his/her risk perception of the risk factor. Hence the present study has been undertaken aiming at determining the Iranian healthcare workers' risk perception of the Covid-19 disease and the relevant effective factors. Materials and Methods: This anonymous online survey was conducted in March-Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The perceived risk perception of COVID-19 was higher among participants who experience the infection themselves and/or family members in the same house than others in the study. In the literature, the perceived risk of COVID-19, especially in risk groups as healthcare workers was above the mean score (42)(43)(44). There was a community-based study reported that the perceived risk of COVID-19 level was higher among United Kingdom citizens with a history of COVID-19 than other individuals in 2021 (45) and there was also a study reporting that there was no relationship between a getting COVID-19 infection and risk perception among Turkish nurses (46).…”
Section: Discussionmentioning
confidence: 97%
“…The perceived risk perception of COVID-19 was higher among participants who experience the infection themselves and/or family members in the same house than others in the study. In the literature, the perceived risk of COVID-19, especially in risk groups as healthcare workers was above the mean score (42)(43)(44). There was a community-based study reported that the perceived risk of COVID-19 level was higher among United Kingdom citizens with a history of COVID-19 than other individuals in 2021 (45) and there was also a study reporting that there was no relationship between a getting COVID-19 infection and risk perception among Turkish nurses (46).…”
Section: Discussionmentioning
confidence: 97%
“…In a study, the rate of disease transmission to healthcare workers was reported as 29% (6). In Iran, more than 6,000 healthcare workers have been infected by COVID-19, and more than 150 of them have died (7).…”
Section: Introductionmentioning
confidence: 99%